Heat transfer enhancement in a rectangular channel with twisted tape inserts - Nuthong, W.; Eiamsa-Ard, S.; Nanan, K.; Eiamsa-Ard, P.; Thianpong, C. (My University, 2009)
Experimental investigation of heat transfer and friction factor behaviors in a rectangular channel with multiple twisted tapes (MTTs) is carried out. In each run, five MTTs are simultaneously used as the swirl flow generators in a test section. The lower wall of the channel is subjected to uniform heat flux conditions while the upper wall is insulated. Parametric runs are made for Reynolds numbers ranging from 2700 to 9000, the tapes with twist-length to twist-width ratios (y/w) of 3, 4 and 5 while the aspect ratio of AR = W/H = 10 is fixed throughout. Experiments using smooth channel are also performed for comparison. The experimental results reveal that heat transfer in the channels with MTTs at twist ratios (y/w) of 3, 4 and 5 are respectively increased around 55%, 37% and 22% over those in the smooth channel. In addition, the empirical correlations of the Nusselt number and friction factor in the developed flow region for the channels fitted with MTTs are also derived.
Keywords: Friction factor; Heat transfer enhancement; Swirl flow; Turbulence flow; Twisted tape